Rarity of microsatellite alterations in acute myeloid leukaemia. - Sill, H. (Nature Publishing Group, 1996)
We have analysed samples from 20 patients with acute myeloid leukaemia for microsatellite alterations by comparing constitutional DNA and DNA from leukaemic samples. Twelve microsatellites were amplified by PCR and investigated for novel bands, indicative of microsatellite instability, or for loss of heterozygosity. Out of 215 paired amplifications, no additional bands were observed at any locus in any of the samples analysed and loss of heterozygosity was found only as four loci from three patients. These results suggest that microsatellite alterations are very uncommon in acute myeloid leukaemia. IMAGES: